A social-ecological approach to managing agricultural ammonia emissions and nitrogen deposition in Rocky Mountain National Park - Piña, Aaron Joshua, author; Denning, A. Scott, advisor; Ojima, Dennis S., advisor; Schumacher, Russ S., committee member; Baron, Jill S., committee member; Ham, Jay M., committee member (Colorado State University. Libraries, 2017)
Atmospheric nitrogen (N) deposition is harmful to nutrient-limited mountain ecosystems. Annual wet deposition of total inorganic N in Rocky Mountain National Park (RMNP) is dominated by ammonium, which primarily comes from agricultural sources. The most wet N deposition events between 1980 and 2015 occurred during summer months. The confluence of summertime mountain meteorology and the location of pollution sources are a perfect combination that leads to high values of wet N deposition in RMNP. In Chapter 2, we tested the importance of convection as a N transport mechanism in addition to large-scale east winds, typically associated with the summertime mountain-valley circulation on the eastern plains of Colorado. We characterized the meteorological transport by using the Weather Research and Forecasting model at 4/3-km horizontal resolution. We used passive tracers as a simplified representation of emissions from a single agricultural source in eastern Colorado during three summer precipitation events where wet N deposition values in RMNP were among the highest recorded in all summers between 1980 and 2015. In all three cases, anticyclones in north-central United States and monsoonal flow associated with the North American Monsoon brought together the necessary conditions for deep convection over RMNP. Output from our simulations suggested large-scale winds were responsible for slow and steady transport whereas convection was a rapid and intermittent form of transport. This chapter showed two scales of transport had an additive effect that led to high deposition of N in RMNP during the afternoon/evening hours of three case studies. Chapter 3 discusses the development of a pilot early warning system (PEWS) for agricultural operators to voluntarily and temporarily minimize emissions of NH3 during periods of upslope winds. The PEWS was created using trajectory analyses driven by outputs from an ensemble of numerical weather forecasts together with the climatological expertise of human forecasters. In this study, we discuss the methods for the PEWS and offer a preliminary analyses of 21 months of the PEWS based on deposition data from two sites in RMNP as wells as voluntary responses from agriculture managers and producers after warnings were issued. Results from this study showed that the PEWS accurately predicted 5 of 7 high N deposition weeks at the lower-elevation observation site, but only 3 of 8 high N deposition weeks at the higher-elevation observation site. With the higher-elevation site receiving pollution from sources both west and east of the Continental Divide, sources west of the Continental Divide would need to be included in the PEWS to capture all of the sources leading to deposition at the higher-elevation site. Sixty agricultural producers and managers from 39 of Colorado's agricultural operations volunteered for the PEWS, and a two-way line of communication between the producers and the scientists was formed. An average of 21 voluntary responses (s.d. 4.9) per warning occurred, with over 75% of the PEWS participants altering their practices after an alert. Solving a broad and complex social-ecological problem requires both a technological approach, such as the PEWS, and collaboration and trust from all participants, including agricultural producers, university researchers, and environmental agencies. Chapter 4 applies a systems approach that explores the actors involved in a complex social-ecological problem that deals with the competing interests of an unadulterated environment and the contribution towards feeding the global population. Agricultural operations in northeastern Colorado are among the densest in the world. The demand of a growing global population has put pressure on the agricultural community to provide large quantities of food in a short amount of time. The cost for higher yields means more water, nutrients, and energy, and the result is environmental degradation in the forms of atmospheric and water pollution. The problem becomes more complex when we mix bottom-up and top-down management approaches. That is, agricultural producers are asked to work together with state and federal agencies on reducing emissions from their operations. A pilot early warning system employed in Colorado since 2014 helped bring together the actors to work towards the common goal of reducing nitrogen deposition in Rocky Mountain National Park. Our goal in this chapter was to organize the problem using a conceptual, social-ecological framework. The case studies and pilot early warning system from Chapters 1 and 2 document starting points for how institutional decisions can incorporate agricultural stakeholders in a mix of bottom-up and top-down management approaches under current and future climatic conditions.